Gradient hydrogel and density difference driven bidirectional self-growth preparation method thereof
The preparation of gradient hydrogels through a two-way self-growth method driven by density difference has solved the problems of complex process and low sensitivity in the prior art, and achieved the effect of high sensitivity and wide sensing range, which is suitable for applications in the soft electronic field.
Patent Information
- Application Number
- CN202510220382.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-02-27
AI Technical Summary
The prior art has problems such as complex process, harmful chemicals, low sensitivity, and poor interface interactions when preparing gradient hydrogels, making it difficult to achieve skin-like sensitivity and timely response to complex mechanical stimuli.
Gradient hydrogels are prepared by a two-way self-growth method driven by density difference. A mixed solution of alkali and salt is used as the bottom solution. A mixed solution of polymer monomer, polyphenol, ammonium persulfate and N,N'-methylenebisacrylamide is spread over the bottom solution. Free radicals are formed through redox reactions to promote polymerization and crosslinking, thereby achieving the formation of gradient structures.
It realizes the simple and rapid preparation of gradient hydrogels, has high sensitivity, wide sensing range, good stability, and does not produce harmful substances. It is suitable for monitoring of motion behaviors with micro deformation and high stress.
Smart Images

Figure CN119708385A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional materials, and in particular relates to a gradient hydrogel and a method for preparing the same by driving bidirectional self-growth thereof with density difference. Background Art
[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] The unique gradient structure of human skin gives it remarkable functionality, extending from the epidermis to the dermis and subcutaneous tissue, with excellent adaptability and flexibility, and can effectively perform protective, sensory and regulatory functions. By mimicking the structural and functional properties of human skin, researchers have developed a variety of highly sensitive and wide-range detection devices and used them in different application scenarios (such as medical engineering, smart prostheses, bionic robots, etc.). As a bionic skin material, hydrogels show great potential in bionic sensor applications due to their excellent flexibility, biocompatibility, excellent conductivity and tunability. Endowing hydrogels with gradient microstructures is an effective strategy to broaden their application areas in bionic sensors, but it remains a challenge to achieve skin-like sensitivity and timely response to complex mechanical stimuli.
[0004] In order to simulate the gradient structure of the skin, various gradient hydrogels have been studied to explore their potential applications in more complex scenarios. Biomimetic gradient hydrogels usually have gradient structures in cross-linking density and component distribution. Researchers have explored various strategies to prepare gradient hydrogels, including gravity induction, electric field / magnetic field stimulation, 3D printing technology, etc. By applying additional electrical or magnetic stimulation, the distribution of charged components can be reconfigured, thereby affecting the pore channels and the cross-linked network structure of the hydrogel. It is also a desirable method to combine single-layer hydrogels with different properties using electrostatic interactions, hydrogen bonds or interpenetrating aggregate networks to prepare double-layer or multi-layer gradient hydrogels. However, the above methods still have the disadvantages of complex preparation process, production of harmful chemicals, low sensitivity, and poor interfacial interactions. Therefore, there is an urgent need to develop a simple and rapid method to prepare gradient hydrogels. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a gradient hydrogel and a method for preparing the same by bidirectional self-growth driven by density difference.
[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions: In a first aspect, the present invention provides a method for preparing a gradient hydrogel by density difference driven bidirectional self-growth, comprising the following steps: A mixed solution of alkali and salt is used as a bottom solution; A mixed solution of polymer monomers, polyphenols, ammonium persulfate and N,N'-methylenebisacrylamide is spread on the bottom solution, and allowed to stand at 15-35°C for a set reaction time to obtain the product.
[0007] The high-concentration / high-density salt solution can be separated from the upper low-density solution to form an initial phase-separated solution, which is beneficial to the subsequent self-growth reaction.
[0008] The stable complex formed by salts such as lithium chloride and the catechol part of polyphenols under alkaline conditions helps to achieve the redox balance between catechol and quinone, thereby promoting free radical polymerization reactions.
[0009] After polymerization, the polymer monomers form polymer chains, which serve as the skeleton of the hydrogel. Polyphenols participate in redox reactions, generate free radicals, and promote monomer polymerization. Ammonium persulfate is an initiator, and N,N'-methylenebisacrylamide is a crosslinker.
[0010] In some embodiments, a mixed solution of polymer monomers, polyphenols, ammonium persulfate and N,N'-methylenebisacrylamide is injected along the container wall at a low speed and spread on top of the bottom solution due to the density difference.
[0011] The low speed is sufficient as long as the mixed solution of polymer monomers, polyphenols, ammonium persulfate and N,N'-methylenebisacrylamide can be spread on the bottom solution to avoid the two solutions from mixing with each other.
[0012] In some embodiments, the base is potassium hydroxide or sodium hydroxide.
[0013] In some embodiments, the salt is lithium chloride, sodium chloride, or zinc chloride.
[0014] In some embodiments, in the bottom solution, the concentration of the base is 0.03-0.05 g / ml, and the concentration of the salt is 0.08-0.5 g / ml.
[0015] In some embodiments, the polymer monomer is acrylamide or acrylic acid.
[0016] In some embodiments, the polyphenol is lignin, tannic acid, catechol, dopamine, or vanillin.
[0017] In some embodiments, in the mixed solution of the polymer monomer, polyphenol, ammonium persulfate and N,N'-methylenebisacrylamide, the concentration of the polymer monomer is 0.5-1.5 g / ml, the concentration of the polyphenol is 4-10 mg / ml, the concentration of ammonium persulfate is 4-10 mg / ml, and the concentration of N,N'-methylenebisacrylamide is 0.1-0.8 mg / ml.
[0018] In some embodiments, the static reaction time is 0.1-1 h.
[0019] In a second aspect, the present invention provides a gradient hydrogel prepared by the preparation method.
[0020] In a third aspect, the present invention provides use of the gradient hydrogel in preparing a pressure sensor.
[0021] The beneficial effects achieved by one or more embodiments of the present invention are as follows: In the present invention, a precursor solution containing polymer monomers (such as polymer monomers such as acrylamide and acrylic acid) is slowly added to a high-concentration salt solution (such as lithium chloride, sodium chloride, etc.). Due to the density difference between the two solutions, redox-induced free radical polymerization forms a barrier layer. Due to the generation of free radicals and subsequent heat release, the interface is immediately ignited by a strong redox reaction. At the same time, free radicals undergo polymerization / gelation reactions from the interface to both sides, causing the hydrogel to show a bidirectional self-growth trend.
[0022] The polymerization / gelation differences are caused by the difference in precursor concentrations between the upper and lower layers. From top to bottom, the cross-linking density of the prepared hydrogel decreases. The bottom layer has a lower degree of cross-linking and a softer structure, but has a higher sensitivity as a strain sensor and is called the soft end. In contrast, the top layer with a high degree of cross-linking (high polymer network density) has a dense structure and excellent mechanical properties and is called the hard end. This strategy represents a major advance in the development of biomimetic gradient hydrogels and provides a novel design option for functional materials.
[0023] When subjected to less pressure, the soft end can show a larger deformation, making the hydrogel highly sensitive. When subjected to greater pressure, the hard end has a dense network structure, so that the hydrogel structure will not be damaged, giving the hydrogel sensor a wide sensing range and good stability. The hydrogel simultaneously exhibits high sensitivity, a wide sensing range, good stability and a simple / fast preparation process, making it suitable for monitoring movement behavior under micro-deformation and high stress. This work not only opens up a new field for the preparation of gradient hydrogels, but also significantly expands its application in the field of soft electronics.
[0024] The preparation method of the present invention is simple, practical, and easy to promote. It does not require other stimulations at room temperature and does not produce other harmful substances. The gradient hydrogel can be obtained through self-growth in just a few minutes.
[0025] The present invention has excellent universality. The prepared gradient hydrogel can adjust its mechanical properties, electrical conductivity and shape by changing the mold salt concentration, shape, salt composition, polyphenol and monomer types, etc., to meet different application requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0027] Figure 1 is a scanning electron microscope (SEM) image of the gradient hydrogel prepared in Example 1 of the present invention.
[0028] Figure 2 1 is a compressive stress test diagram of the hydrogel prepared in Examples 1-5 of the present invention; wherein a is a mechanical property test comparison diagram of the gradient hydrogel of Examples 1-5; b is a conductive property test diagram of the gradient hydrogel of Examples 1-5.
[0029] Figure 3 are actual pictures of different morphologies of the gradient hydrogel prepared in Example 4 of the present invention; Figure 4 This is a sensing performance test diagram of the gradient hydrogel pressure sensor prepared in Example 4 of the present invention, wherein a is a resistance comparison diagram of the gradient hydrogel under different pressures, b is a pressure sensing sensitivity characterization diagram of the gradient hydrogel, and c is a characterization diagram of the response time and recovery time of the gradient hydrogel. DETAILED DESCRIPTION
[0030] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0031] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0032] Example 1 A method for preparing a gradient hydrogel by density difference driven bidirectional self-growth comprises the following steps: To prepare the gradient hydrogel, 4 g acrylamide, 30 mg sodium lignin sulfonate, 30 mg ammonium persulfate, and 2 mg N,N'-methylenebisacrylamide were first added to 5 mL deionized water and stirred at room temperature to prepare a uniform solution as the upper layer.
[0033] Subsequently, 0.168 g potassium hydroxide and 0.424 g lithium chloride were added to 5 ml deionized water and stirred at room temperature to prepare a uniform solution as the bottom layer. Then, the bottom layer solution was poured into the container first, and then the upper layer solution was slowly poured along the container wall to prevent the two solutions from mixing due to shaking. The above solution was then placed at room temperature to obtain a gradient hydrogel.
[0034] The gradient hydrogel was connected to a texture analyzer and then to a digital source meter to monitor the change in electrical resistance during repeated compression of the hydrogel.
[0035] Example 2 A method for preparing a gradient hydrogel by density difference driven bidirectional self-growth comprises the following steps: To prepare the gradient hydrogel, 4 g acrylamide, 30 mg sodium lignin sulfonate, 30 mg ammonium persulfate, and 2 mg N,N'-methylenebisacrylamide were first added to 5 mL deionized water and stirred at room temperature to prepare a uniform solution as the upper layer.
[0036] Subsequently, 0.168 g potassium hydroxide and 0.848 g lithium chloride were added to 5 ml deionized water and stirred at room temperature to prepare a uniform solution as the bottom layer. Then, the bottom layer solution was poured into the container first, and then the upper layer solution was slowly poured along the container wall to prevent the two solutions from mixing due to shaking. The above solution was then placed at room temperature to obtain a gradient hydrogel.
[0037] The gradient hydrogel was connected to a texture analyzer and then to a digital source meter to monitor the change in electrical resistance during repeated compression of the hydrogel.
[0038] Example 3 A method for preparing a gradient hydrogel by density difference driven bidirectional self-growth comprises the following steps: To prepare the gradient hydrogel, 4 g acrylamide, 30 mg sodium lignin sulfonate, 30 mg ammonium persulfate, and 2 mg N,N'-methylenebisacrylamide were first added to 5 mL deionized water and stirred at room temperature to prepare a uniform solution as the upper layer.
[0039] Subsequently, 0.168 g potassium hydroxide and 1.272 g lithium chloride were added to 5 ml deionized water and stirred at room temperature to prepare a uniform solution as the bottom layer. Then, the bottom layer solution was poured into the container first, and then the upper layer solution was slowly poured along the container wall to prevent the two solutions from mixing due to shaking. The above solution was then placed at room temperature to obtain a gradient hydrogel.
[0040] The gradient hydrogel was connected to a texture analyzer and then to a digital source meter to monitor the change in electrical resistance during repeated compression of the hydrogel.
[0041] Example 4 A method for preparing a gradient hydrogel by density difference driven bidirectional self-growth comprises the following steps: To prepare the gradient hydrogel, 4 g acrylamide, 30 mg sodium lignin sulfonate, 30 mg ammonium persulfate, and 2 mg N,N'-methylenebisacrylamide were first added to 5 mL deionized water and stirred at room temperature to prepare a uniform solution as the upper layer.
[0042] Subsequently, 0.168 g potassium hydroxide and 1.696 g lithium chloride were added to 5 ml deionized water and stirred at room temperature to prepare a uniform solution as the bottom layer. Then, the bottom layer solution was first poured into a container (the container shapes were pyramid, cylinder, flower and cube structures), and then the upper layer solution was slowly poured along the container wall to prevent the two solutions from mixing due to shaking. The above solution was then placed at room temperature to obtain a gradient hydrogel.
[0043] The gradient hydrogel was connected to a texture analyzer and then to a digital source meter to monitor the change in electrical resistance during repeated compression of the hydrogel.
[0044] Example 5 A method for preparing a gradient hydrogel by density difference driven bidirectional self-growth comprises the following steps: To prepare the gradient hydrogel, 4 g acrylamide, 30 mg sodium lignin sulfonate, 30 mg ammonium persulfate, and 2 mg N,N'-methylenebisacrylamide were first added to 5 mL deionized water and stirred at room temperature to prepare a uniform solution as the upper layer.
[0045] Subsequently, 0.168 g potassium hydroxide and 2.119 g lithium chloride were added to 5 ml deionized water and stirred at room temperature to prepare a uniform solution as the bottom layer. Then, the bottom layer solution was poured into the container first, and then the upper layer solution was slowly poured along the container wall to prevent the two solutions from mixing due to shaking. The above solution was then placed at room temperature to obtain a gradient hydrogel.
[0046] The gradient hydrogel was connected to a texture analyzer and then to a digital source meter to monitor the change in electrical resistance during repeated compression of the hydrogel.
[0047] Example 6 A method for preparing a gradient hydrogel by density difference driven bidirectional self-growth comprises the following steps: To prepare the gradient hydrogel, 4 g acrylic acid, 30 mg sodium lignin sulfonate, 30 mg ammonium persulfate, and 2 mg N,N'-methylenebisacrylamide were first added to 5 mL deionized water and stirred at room temperature to prepare a uniform solution as the upper layer.
[0048] Subsequently, 0.168 g potassium hydroxide and 2.119 g lithium chloride were added to 5 ml deionized water and stirred at room temperature to prepare a uniform solution as the bottom layer. Then, the bottom layer solution was poured into the container first, and then the upper layer solution was slowly poured along the container wall to prevent the two solutions from mixing due to shaking. The above solution was then placed at room temperature to obtain a gradient hydrogel.
[0049] The gradient hydrogel was connected to a texture analyzer and then to a digital source meter to monitor the change in electrical resistance during repeated compression of the hydrogel.
[0050] Example 7 A method for preparing a gradient hydrogel by density difference driven bidirectional self-growth comprises the following steps: To prepare the gradient hydrogel, 4 g acrylamide, 30 mg alkali lignin, 30 mg ammonium persulfate, and 2 mg N,N'-methylenebisacrylamide were first added to 5 mL deionized water and stirred at room temperature to prepare a uniform solution as the upper layer.
[0051] Subsequently, 0.168 g potassium hydroxide and 2.119 g lithium chloride were added to 5 ml deionized water and stirred at room temperature to prepare a uniform solution as the bottom layer. Then, the bottom layer solution was poured into the container first, and then the upper layer solution was slowly poured along the container wall to prevent the two solutions from mixing due to shaking. The above solution was then placed at room temperature to obtain a gradient hydrogel.
[0052] The gradient hydrogel was connected to a texture analyzer and then to a digital source meter to monitor the change in electrical resistance during repeated compression of the hydrogel.
[0053] Example 8 A method for preparing a gradient hydrogel by density difference driven bidirectional self-growth comprises the following steps: To prepare the gradient hydrogel, 4 g acrylamide, 30 mg sodium lignin sulfonate, 30 mg ammonium persulfate, and 2 mg N,N'-methylenebisacrylamide were first added to 5 mL deionized water and stirred at room temperature to prepare a uniform solution as the upper layer.
[0054] Subsequently, 0.168 g potassium hydroxide and 1.8 g sodium chloride were added to 5 ml deionized water and stirred at room temperature to prepare a uniform solution as the bottom layer. Then, the bottom layer solution was first poured into the container, and then the upper layer solution was slowly poured along the container wall to prevent the two solutions from mixing due to shaking. The above solution was then placed at room temperature to obtain a gradient hydrogel.
[0055] The gradient hydrogel was connected to a texture analyzer and then to a digital source meter to monitor the change in electrical resistance during repeated compression of the hydrogel.
[0056] Example 9 A method for preparing a gradient hydrogel by density difference driven bidirectional self-growth comprises the following steps: To prepare the gradient hydrogel, 4 g acrylamide, 30 mg sodium lignin sulfonate, 30 mg ammonium persulfate, and 2 mg N,N'-methylenebisacrylamide were first added to 5 mL deionized water and stirred at room temperature to prepare a uniform solution as the upper layer.
[0057] Subsequently, 0.168 g of sodium hydroxide and 2.119 g of lithium chloride were added to 5 ml of deionized water and stirred at room temperature to prepare a uniform solution as the bottom layer. Then, the bottom layer solution was poured into the container first, and then the upper layer solution was slowly poured along the container wall to prevent the two solutions from mixing due to shaking. The above solution was then placed at room temperature to obtain a gradient hydrogel.
[0058] The gradient hydrogel was connected to a texture analyzer and then to a digital source meter to monitor the change in electrical resistance during repeated compression of the hydrogel.
[0059] Example 10 A method for preparing a gradient hydrogel by density difference driven bidirectional self-growth comprises the following steps: To prepare the gradient hydrogel, 4 g acrylamide, 30 mg sodium lignin sulfonate, 30 mg ammonium persulfate, and 2 mg N,N'-methylenebisacrylamide were first added to 5 mL deionized water and stirred at room temperature to prepare a uniform solution as the upper layer.
[0060] Subsequently, 4 g of zinc chloride was added to 5 ml of deionized water and stirred at room temperature to prepare a uniform solution as the bottom layer. Then, the bottom layer solution was first poured into the container, and then the upper layer solution was slowly poured along the container wall to prevent the two solutions from mixing due to shaking. The above solution was then placed at room temperature to obtain a gradient hydrogel.
[0061] The gradient hydrogel was connected to a texture analyzer and then to a digital source meter to monitor the change in electrical resistance during repeated compression of the hydrogel.
[0062] The above-mentioned density difference driven bidirectional self-growing gradient hydrogel was characterized and its performance was tested. Figures 1 to 4 shown.
[0063] Figure 1 This is a scanning electron microscope image of the gradient hydrogel prepared in Example 1. It can be seen that the gradient hydrogel has a certain cross-linking gradient, the top layer has a dense structure and excellent mechanical properties, and the bottom layer has a low degree of cross-linking and a soft texture.
[0064] Figure 2 2M is the gradient hydrogel prepared in Example 1, 4M is the gradient hydrogel prepared in Example 2, 6M is the gradient hydrogel prepared in Example 3, 8M is the gradient hydrogel prepared in Example 4, and 10M is the gradient hydrogel prepared in Example 5. The above concentrations are all the concentrations of lithium chloride in the bottom solution. Figure 2 As shown in Figure a, as the concentration of lithium chloride in the bottom solution increases, the compressive stress and compression modulus of the prepared gradient hydrogel decrease successively. Figure 2As shown in Figure b, as the ion concentration increases from 2 M to 8 M, the conductivity of the gradient hydrogel increases. When the ion concentration in the bottom solution reaches 8 M, the conductivity reaches its maximum value. In addition, due to the penetration and diffusion of ions, the ion concentration gradually decreases from the bottom layer to the upper layer along the gradient hydrogel, resulting in a gradient distribution of ions from the soft end to the hard end. In summary, by adjusting the ion concentration in the bottom layer, the mechanical properties and conductivity of the gradient hydrogel can be adjusted to meet different application requirements.
[0065] Figure 3 These are actual pictures of different morphologies of the gradient hydrogel prepared in Example 4 of the present invention. It can be seen that gradient hydrogels of different shapes can be prepared by using containers of different shapes to meet different application requirements.
[0066] Figure 4 is a test diagram of the sensing performance of the gradient hydrogel pressure sensor prepared in Example 4 of the present invention. Figure 4 As shown in a, the gradient hydrogel sensor produces clear resistance changes under different pressures; Figure 4 As shown in Figure b, the sensitivity of the gradient hydrogel sensor in the range of 0-5 kPa is 44 Pa -1 ; In the range of 0-1 kPa, the sensitivity can reach 51.6Pa -1 ;according to Figure 4 As shown in Figure c, the gradient pressure response time is 321 ms and the recovery time is 345 ms.
[0067] Table 1 is a comparison table of the strain of the gradient hydrogels prepared in Examples 4 and 6-10 of the present invention as a function of pressure. It can be seen that the gradient hydrogels prepared with different components have excellent deformation capabilities under different pressure conditions, indicating that the preparation method of the gradient hydrogel has good universality.
[0068] Table 1 is a comparison table of the strain of the gradient hydrogels in Examples 4, 6-10 as a function of pressure
[0069] It can be seen that the density difference-driven bidirectional self-growing gradient hydrogel prepared by the present invention has a significant gradient structure. By adjusting the mold shape, salt concentration, shape, salt composition, polyphenol and monomer type, its stress strain, sensitivity, conductivity and morphology can be adjusted, which well solves the shortcomings of the existing density difference-driven bidirectional self-growing gradient hydrogel, such as complex mechanical preparation process, generation of harmful chemicals, low sensitivity, poor interface interaction, etc. The constructed pressure sensor has stable output performance, high sensitivity and wide detection range, creating favorable conditions for the development of flexible wearable electronic devices.
[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a gradient hydrogel by density difference driven bidirectional self-growth, characterized in that: The steps include: A mixed solution of alkali and salt is used as a bottom solution, wherein the concentration of alkali is 0.03-0.05 g / ml and the concentration of salt is 0.08-0.5 g / ml; Spreading a mixed solution of polymer monomers, polyphenols, ammonium persulfate and N,N'-methylenebisacrylamide on the top of the bottom solution, and standing at 15-35°C for a set reaction time to obtain; In the mixed solution of the polymer monomer, polyphenol, ammonium persulfate and N,N'-methylenebisacrylamide, the concentration of the polymer monomer is 0.5-1.5 g / ml, the concentration of the polyphenol is 4-10 mg / ml, the concentration of the ammonium persulfate is 4-10 mg / ml, and the concentration of the N,N'-methylenebisacrylamide is 0.1-0.8 mg / ml.
2. The density difference driven bidirectional self-growth preparation method of gradient hydrogel according to claim 1, characterized in that: A mixed solution of polymer monomers, polyphenols, ammonium persulfate and N,N'-methylenebisacrylamide is injected along the container wall at a low speed and spread on the bottom solution due to the density difference.
3. The density difference driven bidirectional self-growth preparation method of gradient hydrogel according to claim 1, characterized in that: The alkali is potassium hydroxide or sodium hydroxide; the salt is lithium chloride, sodium chloride or zinc chloride.
4. The density difference driven bidirectional self-growth preparation method of gradient hydrogel according to claim 1, characterized in that: The polymer monomer is acrylamide or acrylic acid.
5. The density difference driven bidirectional self-growth preparation method of gradient hydrogel according to claim 1, characterized in that: The polyphenol is lignin, tannic acid, catechol, dopamine or vanillin.
6. The density difference driven bidirectional self-growth preparation method of gradient hydrogel according to claim 1, characterized in that: The standing reaction time is 0.1-1h.
7. A gradient hydrogel, characterized in that: Prepared by the preparation method described in any one of claims 1 to 6.
8. Use of the gradient hydrogel according to claim 7 in preparing a pressure sensor.
Citation Information
Patent Citations
Dual-network gradient gel for 3D printing and preparation method and application thereof
CN117467163A
Preparation method of biomedical hydrogel with gradient structure
CN119264508A
Electric field induced graded hydrogel films
US20230323040A1